Novel Walking Robot based on the Design of Origami Mechanism - Xinyang Jiang; Yong Xu; Yan Wang; Jiali Liu; Chuansen Zhao; Lü Yeping; Yu Wang (Jixie chuandong)
In view of the limitations of walking robots such as complex driving and inability to adapt to different walking environments， a new type of single-degree-of-freedom walking robot with two leg origami configurations based on the origami mechanism is designed， by folding Miura origami crease angle theory is combined with leg equivalent kinematics model， the kinematics solution is simplified and a new driving mode is designed. The theory of single-vertex origami is extended to the multi-vertex origami configuration， and the definite relationship between the crease corners of different units is obtained. A gait plan that matches the folding state of origami is proposed. The simulation results show that the origami configuration of the robot legs can achieve a long-span and long-span walking gait. Due to the large-span motion at the end of the foot， it does not slide relative to the ground， can achieve smooth walking on roads of different complexity.